The Role of Gender in the Association Among the Emotional Intelligence, Anxiety and Depression - Sergi, Maria Rita; Picconi, Laura; Tommasi, Marco; Saggino, Aristide; Ebisch, Sjoerd J. H.; Spoto, Andrea (Frontiers in Psychology, 2021)
Recent epidemiological data show an increase of depression and anxiety that cause a loss of about 3-4% of the gross domestic product in Europe, as a consequence of a reduced productivity and a premature death of people. Gender differences in both psychopathologies were found from mid-to-late adolescence until 55 years, and data indicate an increase of depression in women. Considering these data, new interventions focused on promoting psychological well-being were designed. A predictive factor of psychological disorders is Emotional Intelligence (EI), the ability to understand and regulate our own emotions, as well as those of others. EI is associated with psychological well-being, as well as with the treatment of mental illness, but gender differences in the association among EI, anxiety and depression remains unclear. The present study aims at analyzing the nomological associations among EI, anxiety and depression. Furthermore, the possible moderating role of gender in the relation between EI, depression and anxiety is investigated in a sample of 1725 healthy participants. Our results show that the ability to recognize and to control emotions in the social context helps us to reduce the risk to be affected by depression and anxiety. Moreover, our study shows that the association of EI with anxiety and depression wasn’t gender moderated. In conclusion, the findings highlight that EI can help people to manage emotions linked to negative events and to successfully understand emotions in others. In addition, we found no moderation role of gender in the association between EI, anxiety and depression.